Results of a phase I–II study of adjuvant concurrent carboplatin and accelerated radiotherapy for triple negative breast cancer - Silvia C. Formenti; Encouse B. Golden; Judith D. Goldberg; Xiaochun Li; Jessica Taff; Maria B. Fenton-Kerimian; Sharanya Chandrasekhar; Sandra Demaria; Yelena Novik (OncoImmunology, 2017)
Purpose: To determine feasibility and explore the clinical efficacy of concurrent radiotherapy and carboplatin as adjuvant treatment of triple negative breast cancer (TNBC). Patients and Methods: Women with Stage I-II TNBC were treated after surgery in a phase I–II prospective trial [NCT01289353]. Weekly carboplatin (AUC = 2.0) was delivered for 6 weeks. Concurrent radiotherapy was delivered in the prone position during weeks 2–4, for a total dose of 40.5 Gy in 15 fractions to the breast, and 46.5 Gy in 17 fractions to the tumor bed. Adverse events (AE) were assessed weekly during treatment, once at 45–60 d, and every 6 mo thereafter, using the Common Terminology Criteria for AE (CTCAE) v3.0. Results: A total of 39 patients accrued and 36 received treatment. Eight patients (22%, exact 95% CI: 10%, 39%) developed grade 2 or greater acute radiation dermatitis. Overall, grade 2 AE were seen in nine and grade 3 in two patients. Twenty-three patients (64%) received additional adjuvant chemotherapy. With a median follow-up of 48 mo, 34/36 (94%) are alive and disease free. One patient died of pulmonary failure with possible but unproven breast cancer recurrence, and one patient died of pelvic malignancy. One patient recurred locally and is alive and disease free after surgical management. Brisk lymphocytic infiltrate was present pre-treatment in 39% of 18 patients with evaluable tumor. Conclusions: Adjuvant concurrent carboplatin and prone accelerated radiotherapy is a well-tolerated and promising treatment of early stage TNBC. The observed 3% compares favorably with the expected 30% recurrence rate within 1–4 y from treatment, warranting further studies.